2016
DOI: 10.1007/s00441-016-2540-5
|View full text |Cite
|
Sign up to set email alerts
|

Notch signaling-mediated cell-to-cell interaction is dependent on E-cadherin adhesion in adult rat anterior pituitary

Abstract: The rat anterior pituitary is composed of hormone-producing cells, non-hormone-producing cells (referred to as folliculostellate cells) and marginal layer cells. In the adult rat, progenitor cells of hormone-producing cells have recently been reported to be maintained within this non-hormone-producing cell population. In tissue, non-hormone-producing cells construct homophilic cell aggregates by the differential expression of the cell adhesion molecule E-cadherin. We have previously shown that Notch signaling,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 28 publications
2
22
0
Order By: Relevance
“…And then, we have found the direct interaction between the transmembrane full length Notch3 and E-ca according to the result of Co-IP, which will help disassembled E-ca to relocate to cell membrane. In line with our findings, Kikuchi, et al reported that Notch2 and the ligand Jagged1 were localized within E-cadherin-positive cells in the marginal layer cells [50]. In addition, TD +N3ICD overexpression could amplify the roles of Notch3 signaling pathway when compared with N3ICD overexpression alone.…”
Section: Discussionsupporting
confidence: 92%
“…And then, we have found the direct interaction between the transmembrane full length Notch3 and E-ca according to the result of Co-IP, which will help disassembled E-ca to relocate to cell membrane. In line with our findings, Kikuchi, et al reported that Notch2 and the ligand Jagged1 were localized within E-cadherin-positive cells in the marginal layer cells [50]. In addition, TD +N3ICD overexpression could amplify the roles of Notch3 signaling pathway when compared with N3ICD overexpression alone.…”
Section: Discussionsupporting
confidence: 92%
“…Additional identification of the ligand-exposing cells may further portray the pituitary stem cell niche(s). Remarkably, a recent study showed co-expression of NOTCH2 and JAG1 in the same pituitary stem cells (Batchuluun et al 2017) which is not in line with the model of lateral inhibition. Moreover, in pituitary stem cell-activated conditions of neonatal maturation and somatotrope ablation injury (GH-Cre/ iDTR model), expression of the ligands Jag1 and/or Dll1 was found upregulated in the isolated stem cell populations , Willems et al 2016 ( Table 1), suggesting that NOTCH activation is unfolding between the cells of the stem cell compartment in these activated states.…”
Section: Notch Pathway: Contained Janus-type Regulator Of the Pituitamentioning
confidence: 64%
“…In other tissues, GHRL2 has been found to induce the expression of Cdh1 (encoding E-cadherin) (Werth et al 2010, which may explain their colocalization in pituitary stem cells. In return, E-cadherin is also needed for proper NOTCH signaling as inhibition of E-cadherin function using antibodies decreases the proportion of NOTCH2 + cells with HES1 immunopositivity (Batchuluun et al 2017). Of note, another pathway with NOTCH-like juxtacrine makeup recently described in the pituitary stem cell niche is the ephrin-ephrin receptor system (Vankelecom 2010, Cheung et al 2017.…”
Section: :3mentioning
confidence: 99%
“…Interestingly, these proteins are associated with either adherens or tight junctions. Notch receptors are also localized at adherens junctions in several cell types ( Batchuluun et al, 2017 ; Benhra et al, 2011 ; Hatakeyama et al, 2014 ; Sasaki et al, 2007 ). Therefore, clustering ligands and receptors at cellular junctions might increase the rate of physical binding events and subsequent Notch signaling activity.…”
Section: Introductionmentioning
confidence: 99%